Modified global and modified linear contrast stretching algorithms: New colour contrast enhancement techniques for microscopic analysis of malaria slide images - Aimi Salihah, Abdul-Nasir (Hindawi Publishing Corporation, 2013)
Link to publisher's homepage at http://www.hindawi.com/